In vitro cytotoxicity of oleanolic/ursolic acids-loaded in PLGA nanoparticles in different cell lines - Silva, Amélia M. (2019)
Oleanolic (OA) and ursolic (UA) acids are recognized triterpenoids with anti-cancer properties, showing cell-specific activity that can be enhanced when loaded into polymeric nanoparticles. The cytotoxic activity of OA and UA was assessed by Alamar Blue assay in three different cell lines, i.e., HepG2 (Human hepatoma cell line), Caco-2 (Human epithelial colorectal adenocarcinoma cell line) and Y-79 (Human retinoblastoma cell line). The natural and synthetic mixtures of these compounds were tested as free and loaded in polymeric nanoparticles in a concentration range from 2 to 32 µmol/L. The highest tested concentrations of the free triterpene mixtures produced statistically significant cell viability reduction in HepG2 and Caco-2 cells, compared to the control (untreated cells). When loaded in the developed PLGA nanoparticles, no differences were recorded for the tested concentrations in the same cell lines. However, in the Y-79 cell line, a decrease on cell viability was observed when testing the lowest concentration of both free triterpene mixtures, and after their loading into PLGA nanoparticles.